2004
DOI: 10.1093/tropej/50.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA Antibody Responses in Venezuelan Children Infected with Giardia duodenalis

Abstract: We standardized and evaluated an ELISA technique for the detection of total and specific anti-Giardia duodenalis secretory IgA antibodies (sIgA). Samples of saliva and serum of 161 Venezuelan schoolchildren were analysed. After stool examination, 66 children were diagnosed to be infected with Giardia duodenalis, 22 with other protozoa, and 73 non-parasitized. The mean (+ 2 SD) values of secretory IgA in the non-parasitized group was considered as the criterion of positivity. The levels of total and specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…The levels of serum specific IgA were similar in these groups of children, suggesting that the levels of this antibody may reflect previous exposure to parasitic antigens, rather than current infection (Table 2). Similarly, Rodríguez et al (2004) reported that the levels of total and specific anti-Giardia slgA were significantly higher in children with Giardia compared with the group with other protozoa (p<0.01) and the non-parasitized group (p<0.001). In a study by Cedillo-Rivera et al (2009), positive saliva samples from individuals infected with G. duodenalis contained seven times more sIgA than the saliva samples from non-infected individuals.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The levels of serum specific IgA were similar in these groups of children, suggesting that the levels of this antibody may reflect previous exposure to parasitic antigens, rather than current infection (Table 2). Similarly, Rodríguez et al (2004) reported that the levels of total and specific anti-Giardia slgA were significantly higher in children with Giardia compared with the group with other protozoa (p<0.01) and the non-parasitized group (p<0.001). In a study by Cedillo-Rivera et al (2009), positive saliva samples from individuals infected with G. duodenalis contained seven times more sIgA than the saliva samples from non-infected individuals.…”
Section: Discussionmentioning
confidence: 82%
“…Saliva samples were collected using sterile cotton swabs which were maintained in contact with oral mucosa between the gum and inside of the cheek for 10 min (Rodríguez et al 2004). Saliva secretion was recovered by compression using sterile syringe having 1 ml of cold phosphate-buffered saline (PBS, pH 7.2) into vacutainer tubes with EDTA and stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations